From Campaign to Habit: Evaluating Library Promotion Strategies to Boost Primary Students’ Reading Interest - Supriyatmi Supriyatmi; Yasir Riady; Eka Evriza; Ahmad Jum'a Khatib Nur Ali (Media Akademika Publisher, 2025)
This study evaluates how library promotion strategies can shift primary students from campaign-based participation to sustained reading habits. Conducted at a primary school in Indonesia, the research employed a qualitative descriptive design using observations, semi-structured interviews with librarians, teachers, and students, and document analysis of logs and circulation records, and photographs if available, to document implementation processes closely. Data were coded inductively and triangulated across sources. Three key initiatives emerged: interactive read-aloud sessions, a curated reading corner, and a daily 15-minute independent-reading routine. Together, these initiatives were associated with increases in library visits and borrowing frequency. Read-alouds modeled fluent reading and introduced new vocabulary; the reading corner broadened interest-aligned choice; and the daily window normalized sustained reading. Constraints that moderated impact included limited collection breadth, constrained facilities and opening hours, and uneven teacher participation. Practical implications include pairing read-alouds with brief discussion prompts, maintaining a regularly refreshed, student co-curated reading corner, institutionalizing a short daily reading slot with light scaffolds, and formalizing teacher-librarian planning for collection development and class-linked mini-lessons. The study contributes by reframing promotion from event-based outreach to routine-embedded practice and by clarifying the enabling conditions required to convert promotional visibility into everyday reading behaviors in primary education.